PEMBELAJARAN BAHASA ARAB PADA USIA DEWASA MELALUI PLATFORM YOUTUBE: STUDI ANALISIS AUDIENS BERBASIS DATA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study examines the characteristics of adult learners in Arabic language learning through the YouTube platform in the context of digital-based education. The rapid development of digital technology has transformed learning practices, allowing broader access across different age groups, including adult learners who are often underrepresented in previous studies. This research aims to analyze the demographic profile of Arabic language learners on YouTube and to identify its implications for digital learning strategies. The study employs a quantitative descriptive approach using secondary data obtained from YouTube Analytics within the period of January 1 to September 1, 2025. The data include audience demographics such as age, gender, and geographic distribution. The findings reveal that the majority of learners are in the adult and elderly age groups, particularly those aged 65 years and above, followed by the 55–64 age group, with a dominant proportion of female viewers. Geographically, the audience is largely concentrated in Southeast Asia, especially Malaysia. These results indicate that Arabic language learning via YouTube is significantly utilized by adult learners as part of lifelong learning practices. The study highlights the importance of developing adaptive, accessible, and contextually relevant learning content tailored to adult learners in digital environments.